Profil Pemecahan Masalah Kesebangunan Ditinjau dari Kemandirian Belajar Siswa - Ginanto, Dewa Gede Cahyo; Nasir, Rahma; Hasbi, Muh.; Rizal, Muh. (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to describe student problem solving based on the level of student learning independence. The method used is qualitative descriptive research. The subjects of the study were three students of grade IX D SMPN 7 Palu, who were selected using a learning independence questionnaire, with high, medium, and low categories. The problem-solving indicators used are indicators developed by polya, namely, understanding the problem, making a problem-solving plan, implementing the problem-solving plan, and re-checking. The results showed that subjects with high and medium independence were better at meeting each problem-solving indicator compared to low subjects. So it can be concluded that the higher the learning independence of students, the better the problem solving will be. Keywords: Congruence; Learning Independence; Solution to problem